Creating active boundary conditions with Planar loudspeaker arrays to absorb and reflect sound - Müller, Anthea (My University, 2024)
It was shown in the 1970s that a combination of two secondary sources are able to absorb sound energy in one-dimensional sound propagation in a duct. The primary source can be interpreted as being surrounded by a double-layer of secondary sources. This is inconvenient in two- and three-dimensional scenarios as surfaces of secondary sources have to be used, which are difficult to implement in practice. This thesis demonstrates that the same type of active absorption is possible also in open space, i.e., when the secondary sources do not fully enclose the primary source. In contrast to active noise canceling, the aim here is not to achieve active reduction in the downstream area by increasing the sound level in the upstream area, but rather to actively remove energy from the sound field. The focus here is particularly set on canceling out low frequencies to facilite practical measurements. For this, two boundary conditions are set, one in the upstream and one in the downstream area. To achieve the objective at the boundary conditions a set of FIR filters must be determined. This is done here with the help of the LMS method, which is extended to a MIMO (Multiple Input Multiple Output) system. First the results of Swinbanks for the active reduction inside the one dimensional duct are recreated with simulations and confirmed with an experiment. Based on these findings the approach is first extended two dimensions to perform absorption of cylindrical waves with the help of two line sources and then further extended to three dimensions to perform the absorption of spherical waves by means of one-dimensional distributions of point sources. Two experiments are carried out to confirm or refute the concepts introduced. These are first planned in detail with the help of simulations. The first experiment (Setup 1) demonstrates the active absorption of cylindrical waves emitted by line arrays in an outdoor free field setting. The second experiment (Setup 2) demonstrates the active absorption of sound emitted by a point source that is actively absorbed by curved arrays within a semi-anechoic chamber. The simulation results were confirmed in both setups with the measurement results. They proof that the active control of the downstream area whilst not influencing the upstream area is possible with the proposed boundary conditions within the limitations of the method and their test environments. In both experiments active reduction is achieved throughout the downstream area, achieving an averaged active reduction of 11 dB (3 dB over background noise level) in Setup 1 and an active averaged reduction of -27 dB (1 dB over background noise level) in Setup 2 at the boundary condition. Throughout the upstream area the average deviation from the undisturbed sound-field for Setup 1 is 0.3 dB, for Setup 2 it is 0.08 dB
Keywords: Active Noise Control, Active Sound Absorption, Free Field Absorption, LMS Method